PARTISIPASI PEMUDA DALAM PROGRAM PEMBANGUNANDESA DI DESA BORONG, KECAMATAN HERLANG, KABUPATEN BULUKUMBA - zulaitul Qadar; Ashari Ismail; Mauliadi Ramli (PREDESTINATION: Journal of Society and Culture, 2023)
ABSTRACT This study aims to determine (1) the factors that influence youth participation in village development programs in Borong Village, Herlang District, Bulukumba Regency. (2) Forms of youth participation in village development programs in Borong Village, Herlang District,Bulukumba Regency. The results of this research show A) Factors that influence youth participation in village development programs namely, Internal factors,a) Economic Factors, External Factors, a) community spirit wants youthparticipation in development programs, b) Lack encouragement of youth organizations. B) Forms of  youth participation in village development programs, a) Forms of youth participation in village development programs, namely 1) Participation of ideas or ideas, where youth provide input and ideas regarding development planning, a) Planning for farm roads in Kajang-Kajang Hamlet, b) agricultural training planning. 2) Labor participation, a) Mutual cooperation in cleaning infrastructure, 3) Property participation, a) Youth donatetheir land for the construction of farm roads, b) Youth donate their land for the constructionof children's education facilities.